Avaliação de linhagens do papilomavírus humano (hpv) 16 no câncer de colo do utero e seu impacto na resposta ao tratamento com radioterapia e quimioterapia - FIGUEIREDO , Fábio Vidal de (2019)
Cervical cancer occupies the fourth position in incidence and mortality among women, with 569.847 new cases (6.6%) and 311.365 deaths (7.5%). Its incidence relates to Human Development Index (HDI), although its frequency is declining in developed countries, we observe a burden of new cases in regions less developed, where occurr 80% of cases. High-risk human papillomavirus (HPV) infection are the main cause of cervical câncer. The HPV 16 is responsible for half of the cases of cervical câncer. Several studies suggested that this genetic variability between the HPV16 variants could influence the potential for infection, viral persistence and development of invasive cervical cancer. It was hypothesized that this phylogenetic single-nucleotide polymorphism among HPV 16 lineages and sublineages could provide difference in the response to cervical cancer treatment with radiotherapy and chemotherapy depending of the detected HPV variant. This study aimed to estimate the frequency of Human papilloma virus (HPV) 16 lineages in specimens of cervical cancer, relate the pathological factors in those variants and assess the response to treatment with radical chemoradiotherapy. The population consisted of women forwarde to reference cancer hospital in São Luis-MA, answered sociodemographic data and samples of cervical cancer were collected hospital to test the presence of Human papilloma virus types DNA and variants. The women with HPV -16 lineage treated with chemoradiotherapy, were avaliated after three months to access response to treatment. The standard protocol of the service consisted of cisplatin based chemotherapy 40 mg/m² plus conventional pelvic irradiation in the dosis of 45-50.4 Gy and high dose rate brachytherapy of 28-30 Gy to Point A. HPV DNA was detected in out 104 (88.1%) of the 118 patients. HPV-16 present in 63 patients (53%). Lineages of HPV 16 identified in 57 patients being: 33 (57.8%) lineage A, 2 lineage B (3.5%), 2 lineage C (3.5%) and 20 (35.0%) lineage D. The median age of the patients was 48.4 years (range 25-85 years). Squamous cell carcinoma was detected 48 times (84.2%). Adenocarcinoma were more likely to occur in lineage D, as three of the four cases occurred in this lineage. A total of 11 patientes with HPV-16 variant were treated with chemoradiotherapy. After three months, was observed that nine of the eleven patients (81.8%) achieved complete response: five of the lineage A, two of the lineage C and two of the lineage D. The cases of partial response and progression of disease, one each, occurred in the lineage A. We could not establish a association between HPV-16 lineages and local response to chemoradiotherapy due to small number of patients and irregular distribution of lineages, although the two cases of tumor persistence occurred in patients with lineage D.